Implementasi Kearifan Lokal Melalui Penerapan Baju Adat Kebaya Di Pendidikan Anak Usia Dini - Siti Maisaroh; Dawamatussilmi, Vina; Hidayatu Munawaroh (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2023)
This study aims to investigate how the application of traditional kebaya clothes in early childhood education can integrate local wisdom. Participatory observation and interview methods were used to collect data from teachers and parents. The results of the study show that the application of traditional kebaya clothes helps children understand and appreciate their own culture and broaden their understanding of cultural diversity. This implementation provides benefits in the development of children's cultural identity and increases their self-confidence, creativity and appreciation of cultural diversity. It is important for educational institutions and parents to support such educational programs in early childhood education.